ENVIRONMENTAL ISSUES RELATED TO TIN MINING IN BANGKA BELITUNG ISLANDS: Received: 7th June 2022; Revised: 14th October 2022, 26th October 2022, 2nd November 2022; Accepted: 10th November 2022 - Haryadi, Dwi; Ibrahim, Ibrahim; Darwance, Darwance (PEOPLE: International Journal of Social Sciences, 2022)
Massive tin mining in Bangka Belitung Islands significantly contributes to environmental issues, attracting media attention. For instance, several media continuously report environmental issues concerning tin mining with their respective perspectives. Therefore, this study aimed to describe and determine the news’ perspective concerning the tin mining conflict in Bangka Belitung Islands using literature approach. The results showed that the media attention in reporting on tin mining ranged from reclamation issues, regulations and policies, mining accidents, conflicts, impacts of tin mining, Corporate Social Responsibility (CSR), and law enforcement. This means that the media has not yet reached the investigative stage of discussing certain issues that need in-depth studies. Although the local media have covered various environmental issues, the coverage is only descriptive and not directed towards investigative environmental journalism.